Not all IGHV3-21 chronic lymphocytic leukemias are equal: prognostic considerations - Baliakas, Panagiotis; Agathangelidis, Andreas; Hadzidimitriou, Anastasia; Sutton, Lesley-Ann; Minga, Eva; Tsanousa, Athina; Scarfò, Lydia; Davis, Zadie; Yan, Xiao-Jie; Shanafelt, Tait; Plevova, Karla; Sandberg, Yorick; et al. (Blood, 2015)
An unresolved issue in chronic lymphocytic leukemia (CLL) is whether IGHV3-21 gene usage, in general, or the expression of stereotyped B-cell receptor immunoglobulin defining subset #2 (IGHV3-21/IGLV3-21), in particular, determines outcome for IGHV3-21-utilizing cases. We reappraised this issue in 8593 CLL patients of whom 437 (5%) used the IGHV3-21 gene with 254/437 (58%) classified as subset #2. Within subset #2, immunoglobulin heavy variable (IGHV)-mutated cases predominated, whereas non-subset #2/IGHV3-21 was enriched for IGHV-unmutated cases (P = .002). Subset #2 exhibited significantly shorter time-to-first-treatment (TTFT) compared with non-subset #2/IGHV3-21 (22 vs 60 months, P = .001). No such difference was observed between non-subset #2/IGHV3-21 vs the remaining CLL with similar IGHV mutational status. In conclusion, IGHV3-21 CLL should not be axiomatically considered a homogeneous entity with adverse prognosis, given that only subset #2 emerges as uniformly aggressive, contrasting non-subset #2/IGVH3-21 patients whose prognosis depends on IGHV mutational status as the remaining CLL.
Keywords: senioři; analýza přežití; Gene Expression Regulation, Leukemic; Somatic Hypermutation, Immunoglobulin; Genetic Heterogeneity; somatická hypermutace imunoglobulinových genů; Gene Rearrangement, B-Lymphocyte, Heavy Chain; Survival Analysis; Prognosis; výsledek terapie; Immunoglobulin Heavy Chains; Middle Aged; mužské pohlaví; těžké řetězce imunoglobulinů; Antineoplastic Agents; B-lymfocyty; chronická lymfatická leukemie; ženské pohlaví; prognóza; protinádorové látky; Time-to-Treatment; B-Lymphocytes; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; genetická heterogenita; lidé středního věku; přestavba genů pro těžké řetězce B-lymfocytů; Female; Aged; čas zasáhnout při rozvinutí nemoci; Treatment Outcome; regulace genové exprese u leukemie; lidé; Male